PENGARUH PEMILIHAN ARAH ACUAN 00 DAN ARAH ROTASI PADA ANALISIS KORELASI DAN REGRESI LINIER-SIRKULAR (STUDI KASUS: PETA KAWASAN RAWAN BENCANA LETUSAN GUNUNG - Abdul Aziz Nurussadad; I Made Sumertajaya; Ahmad Ansori Mattjik (FORUM STATISTIKA DAN KOMPUTASI, 2011)
The measurement results doesn't only consist of data with linear attributes, but also data with circular attributes. The circular data has a uniqueness that is not owned by the linear data, circular data is independent of the choice of 0o reference and rotation direction. The uniqueness of circular data analysis is tested in linear circular correlation and linear circular regression. The results of correlation analysis proved that the selection of the reference direction 0o can be done subjectively because the linear circular correlation results show the same value 0.899 for all possible selection of 0o reference and rotation direction. For linear circular regression, the model constructed has a same coefficient of determination that is 0.808 and the same b0, which is 5.231 for all possible selection of 0o reference and rotation direction. Similarly, statistics from the error of linear circular regression analysis have the same value, minimum = -2.693, quartile 1 = -0.835, median = -0.171, quartile 3 = 0.548, maximum = 8.421. Alleged circular linear regression parameters, namely b1 and b2, forming a cycle that each has in common b1 = -1.226 E-07-2.728 cos (α) - 2.655 sin (α) and b2 = 3.061 E-07-2.655 cos (α ) + 2.728 sin (α) where α is the position of the 0o reference direction in degrees on each model. Keywords : Directional Statistics, Circular Statistics, Linear-Circular Regression, Linear Circular Correlation